Faktor - Faktor Yang Mempengaruhi Kecenderungan Penerimaan Opini Audit Going Concern Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2008-2012 - Sihdarma, Shandy Surya; , Dra. Nursiam, Ak, M.H (2014)
This study aims to predict the effect of audit quality, financial condition, the growth of the company, the previous year's audit opinion, firm size, and debtto- equity ratio of the tendency of going-concern audit opinion. In this study the type of data used is quantitative data with a population of 145 companies listed in Indonesia Stock Exchange in 2008-2012. The analytical method used is logistic regression analysis with sample totaling 20 companies were selected based on purposive sampling method for 5 periods. Based on the analysis it can be concluded that the quality of the audit significant negative effect on the going-concern audit opinion, the financial condition of the company has no significant effect on the going-concern audit opinion, the growth of the company has no significant effect on the going-concern audit opinion, the previous year's audit opinion has no effect significantly to the going-concern audit opinion, the size of the company does not have a significant effect on the going-concern audit opinion, and debt-to-equity ratio does not significantly influence the going-concern audit opinion.